Multicomponent System: A Novel Approach in Cocrystal Techniques for Improving the Solubility of Poorly Soluble Drugs - Jawahar, Natarajan; Rao, Roshan Prasad; R, Karnesh; Selvaraj, Jubie; Selvamuthukumar, S (Indian Journal of Pharmaceutical Education and Research, 2025)
Poor solubility in modern pharmaceuticals has been a significant barrier to achieving optimal oral bioavailability. A majority of drug substances and New Chemical Entities (NCEs) are classified under BCS (Biopharmaceutical Classification System) Class II or Class IV. Cocrystals, which are multicomponent systems comprising an Active Pharmaceutical Ingredient (API) and one or more coformers in a specific stoichiometric ratio, have been utilized to address this issue. Furthermore, cocrystals and multicomponent systems have been developed to deliver Fixed-Dose Combinations (FDCs) of two or more drugs simultaneously, leading to the emergence of Drug-Drug Cocrystals (DDCs). They have helped in improving the bioavailability and efficacy of APIs by improving solubility and other factors such as tabletability and flow property. The eventual approval and the release of products such as Beta-Chlor, Suglat, Steglatro, Entresto, Setglujan, and Seglentis demonstrates the capability of DDCs to deliver fixed-dose combinations while achieving success in the market. This review provides a brief introduction to cocrystals as multicomponent systems and describes the feasibility of multicomponent systems, documented research on multicomponent systems and DDCs, identification methods and marketed approvals of DDCs.
Keywords: Cocrystals; Multicomponent Systems; Dissolution Enhancement; Improved; Physicochemical Properties